2022
DOI: 10.5114/reum.2022.123672
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic arthritides: an up-to-date case-based systematic review

Abstract: Among the rheumatic diseases whose symptoms are more often associated with the possibility of cancer and other malignancies are systemic sclerosis, dermatomyositis and rheumatic polymyalgia. However, a differential diagnosis should be performed in each case of non-typical rheumatic disease and/or other neoplastic disease risk factors. The article’s aim was based on a literature review of this subject and presentation own a case description and discussion about arthritis as a paraneoplastic syndrome. The conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Many features of this case are in line with prior PA literature, namely occurrence as symmetrical polyarthritis in a patient >50 years of age showing poor response to standard therapy with NSAIDs, glucocorticoids and DMARDs, yet complete vanishing of joint complaints after cancer treatment [ 2–4 ]. However, PA patients are usually male and seronegative for RF and CCP, which are detectable in only 23% and 11%, respectively [ 2 , 5 ].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Many features of this case are in line with prior PA literature, namely occurrence as symmetrical polyarthritis in a patient >50 years of age showing poor response to standard therapy with NSAIDs, glucocorticoids and DMARDs, yet complete vanishing of joint complaints after cancer treatment [ 2–4 ]. However, PA patients are usually male and seronegative for RF and CCP, which are detectable in only 23% and 11%, respectively [ 2 , 5 ].…”
supporting
confidence: 82%
“…Notably, PA has most often been found in lung adenocarcinoma and haematological malignancies [ 2 ], and the literature yields only two prior reports of adnexal tumour association: one ovarian teratoma in a 34-year-old woman [ 6 ] and one ovarian cystadenocarcinoma in a 64-year-old woman, who, however, had an additional malignant sarcomatoid lung tumour [ 7 ].…”
mentioning
confidence: 99%
“…1,2 A recent systematic review found that the mean age of onset for paraneoplastic arthritis was 53 and was more common in males with the most common pattern of presentation being symmetrical polyarthritis. 2 Our case reflects the majority of paraneoplastic arthritis cases, which are seronegative and demonstrate poor response to NSAIDs, glucocorticoids, or conventional DMARDs. 2 Pulmonary and hematological malignancies are most commonly associated with paraneoplastic arthritis.…”
Section: Case Report: Paraneoplastic Secondary To Ovarian Teratomamentioning
confidence: 78%
“…2 Our case reflects the majority of paraneoplastic arthritis cases, which are seronegative and demonstrate poor response to NSAIDs, glucocorticoids, or conventional DMARDs. 2 Pulmonary and hematological malignancies are most commonly associated with paraneoplastic arthritis. 2,3 Ovarian teratoma is the most common benign tumor in premenopausal women and is often asymptomatic.…”
Section: Case Report: Paraneoplastic Secondary To Ovarian Teratomamentioning
confidence: 78%
See 1 more Smart Citation